1994
DOI: 10.1148/radiology.190.2.8284406
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism: comparison of MR images with radionuclide and angiographic studies.

Abstract: MR imaging reliably depicts large and medium-size pulmonary emboli, regardless of infiltrates or effusion; hence, it may clarify findings on V-P scans that show intermediate probability of pulmonary embolism or are at variance with the clinical impression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…MR angiography is as accurate as CT angiography in demonstrating lobar and segmental emboli (28,29). In a study with angiographic correlation by Erdman et al (30), MR imaging had a sensitivity of 90% and a specificity of 77%, whereas in a study by Gupta et al (29), it had a sensitivity of 85% and a specificity of 96%. Recent MR imaging studies by Hatabu et al (31,32) showed that this modality demonstrates perfusion (31) and ventilation (32) of the lung parenchyma.…”
Section: Acute Pulmonary Embolismmentioning
confidence: 96%
“…MR angiography is as accurate as CT angiography in demonstrating lobar and segmental emboli (28,29). In a study with angiographic correlation by Erdman et al (30), MR imaging had a sensitivity of 90% and a specificity of 77%, whereas in a study by Gupta et al (29), it had a sensitivity of 85% and a specificity of 96%. Recent MR imaging studies by Hatabu et al (31,32) showed that this modality demonstrates perfusion (31) and ventilation (32) of the lung parenchyma.…”
Section: Acute Pulmonary Embolismmentioning
confidence: 96%
“…We excluded 4065 studies after title and abstract screening. Of the 49 retrieved studies, we identified 19 that met all the inclusion criteria [14,17,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]: 16 on a patient basis and nine on a vessel basis ( Figure S1). Two of these articles [27,28] shared the same patient population, but evaluated the diagnostic performance of a combined MRI approach and separate MRI sequences (on a patient-based level), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is also being utilized to evaluate clinically suspected PE (124,125,183,(203)(204)(205)(206). In a comparison of noncontrast-enhanced MRI with spiral CT, the average sensitivity of CT for five observers was 75%; for MRI it was 46%.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%